Advanced Parallel Processing Technologies 9th International Symposium, APPT 2011, Shanghai, China, September 26-27, 2011. Proceedings - Temam, Olivier; Yew, Pen-Chung; Zang, Binyu (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed proceedings of the 9th International Symposium on Advanced Parallel Processing Technologies, APPT 2011, held in Shanghai, China, in September 2011. The 13 revised full papers presented were carefully reviewed and selected from 40 submissions. The papers are organized in topical sections on parallel distributed system architectures, architecture, parallel application and software, distributed and cloud computing.